Evaluation of a biosecurity survey approach for contamination by Chlamydia pecorum in koala rehabilitation, field capture, and captive settings - Casteriano, Andrea; Van Aggelen, Astrid Robin; Fischer, Shali; Flanagan, Cheyne; Marschner, Caroline; Nugent, Hannah; Huston, Wilhelmina; Higgins, Damien P. (PeerJ, 2023)
Transmission of Chlamydia pecorum between koalas is a potential risk in field capture or rehabilitation settings, where koalas are held in proximity to each other, or equipment is shared between animals. Given the impact of C. pecorum on koala welfare and population viability it is surprising that quarantine and disinfection protocols in a koala rehabilitation facility or capture settings have not previously been evaluated. This study aimed to evaluate an approach, based on the detection of chlamydial DNA and cell viability, to determine the degree of environmental contamination within a koala care facility. Various fomite sites associated with koala care at a koala rehabilitation facility in New South Wales, Australia were identified as potential sources of chlamydial contamination, following exposure to koalas known to be infected with C. pecorum. Fomite sites were swabbed following exposure, and again after decontamination procedures were carried out. Samples were tested for the presence of chlamydial DNA using qPCR and viability using both RT-qPCR and cell culture. From a total of 239 sampling events, 30 tested qPCR positive for chlamydial DNA, with 19 and 11 samples corresponding to pre-decontamination and post-decontamination events respectively. Detection of chlamydial DNA appeared to be most common in the examination room, especially on fomite sites in direct contact with koalas. Physical removal of chlamydial DNA, or its degradation by the elements, appeared to be more common on outdoor enclosures, clothing, and hands. Based on the cell culture assay, of the pre-decontamination samples with chlamydial DNA, eight had viable chlamydial cells, two of these at low levels. Of the post-decontamination samples with chlamydial DNA, one had a moderate number, and one had a very low number of viable chlamydial cells. RT-qPCR was unsuccessful in determining cell viability due to low yields of RNA and high levels of contaminants from the environmental samples. The outcomes of this study provide a knowledge base for the design of future biosecurity evaluation guidelines in captive and koala rehabilitation facilities. The higher incidence of chlamydial DNA detection by qPCR than viable organism highlights the need to use viability assays in similar studies. However, further investment is still needed to optimise these methods and improve sensitivity for complex environmental samples.
Keywords: Koala; Chlamydia; Transmission; Fomite; Biosecurity; Chlamydia pecorum